P‐16.7: Optical human‐machine interaction based on sub‐wavelength gratings. (4th October 2019) - Wang, Chengliang; Wang, Haoyu; Fu, Yifei; Ren, Huiling; Huang, Xinran; Wu, Bisheng; Jiang, Shuai; Zheng, Jun; Ye, Zhicheng
Abstract : Optical signals input from a light source are used as media for human‐machine interaction via the coupling of sub‐wavelength gratings covered on the display screen. The system includes a laser pen, a transparent sub‐wavelength grating optical film which couples the incident light into waveguide, and photodetectors set on the sides of the film to sense and decide the position of incident light. Furthermore, we can load the modulated signal on the incident light so that it can transfer data to the display device. The design provides a novel remote 'touch' interaction which is of great practical meaning in the large screen displays.